2018
DOI: 10.3390/rs10020320
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Alpine Grassland Cover Based on Unmanned Aerial Vehicle Technology and Multi-Factor Methods: A Case Study in the East of Tibetan Plateau, China

Abstract: Grassland cover and its temporal changes are key parameters in the estimation and monitoring of ecosystems and their functions, especially via remote sensing. However, the most suitable model for estimating grassland cover and the differences between models has rarely been studied in alpine meadow grasslands. In this study, field measurements of grassland cover in Gannan Prefecture, from 2014 to 2016, were acquired using unmanned aerial vehicle (UAV) technology. Single-factor parametric and multi-factor parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…In each station, the monthly mean air temperature and cumulative precipitation were calculated. Anusplin software package was used to interpolate the station-specific data with thin plate smoothing spline interpolation method [29].…”
Section: Dem Soil and Meteorological Data Preprocessmentioning
confidence: 99%
See 2 more Smart Citations
“…In each station, the monthly mean air temperature and cumulative precipitation were calculated. Anusplin software package was used to interpolate the station-specific data with thin plate smoothing spline interpolation method [29].…”
Section: Dem Soil and Meteorological Data Preprocessmentioning
confidence: 99%
“…Those features are suitable for monitoring of grassland AGB and its dynamic changes especially for large areas [24]. However, univariate parameter RS inversion models based on MODIS data have low accuracy and poor stability in alpine meadow grassland [23], [28], [29], because of the extensive spatial distribution, complex grass species and high spatial heterogeneity [14], [29], [24]. Hence, it is essential to explore a new grassland AGB monitoring method based on MODIS data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NDVI uses red and infrared reflectance, which are sensitive to the soil background [26]. Studies have also shown that the NDVI could be saturated in grasslands with highly fractional vegetation cover [76]. As an improved vegetation index, EVI overcomes these shortcomings [26].…”
Section: Discussionmentioning
confidence: 99%
“…The results are shown in Tables 4 and 5, where Pn represents the average precipitation with a lead time n month, and Tn represents the average precipitation with a lead time n month. With reference to similar studies and the meteorological cycles [32][33][34][35], the maximum lead times were set to 6 months.…”
Section: Predictors Selectionmentioning
confidence: 99%